2002
DOI: 10.2169/internalmedicine.41.30
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Pneumonia due to Persistent Chlamydia Pneumoniae Infection.

Abstract: Twocases of recurrent pneumoniadue to Chlamydia pneumoniae are described. C. pneumoniae was continuously detected from the nasopharynx in both patients by the polymerase chain reaction and/or culture even with appropriate antibiotic therapy during the first episode. After eradication of C. pneumoniae with long-term macrolide therapy, the respiratory symptoms of both patients completely disappeared and no relapse was observed. These data indicate that newtreatment strategies maybe necessary to eradicate the org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Follow-up studies on human ocular and recurrent genital C. trachomatis infections have shown features common to persistent state, such as the frequent detection of chlamydial nucleic acid while the organisms can infrequently be cultured (Hudson et al, 1992; Dean et al, 2000). Clinical data also suggests that C. pneumoniae may persist for months after the initial infection (Grayston, 1992), and persistent lung infections despite of antimicrobial therapy have been reported (Falck et al, 1996; Miyashita et al, 2002). C. trachomatis DNA has been demonstrated by in situ hybridization in the fallopian tube tissue from infertile women (Campbell et al, 1993; Barlow et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up studies on human ocular and recurrent genital C. trachomatis infections have shown features common to persistent state, such as the frequent detection of chlamydial nucleic acid while the organisms can infrequently be cultured (Hudson et al, 1992; Dean et al, 2000). Clinical data also suggests that C. pneumoniae may persist for months after the initial infection (Grayston, 1992), and persistent lung infections despite of antimicrobial therapy have been reported (Falck et al, 1996; Miyashita et al, 2002). C. trachomatis DNA has been demonstrated by in situ hybridization in the fallopian tube tissue from infertile women (Campbell et al, 1993; Barlow et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Somestudies have suggested a possible association of C. pneumoniae infection and acute exacerbations of asthma and chronic obstructive pulmonary disease (2)(3)(4). Seroepidemiological studies showing antibody prevalence rates in a range of 50 to 70%suggest that C. pneumoniae is widely distributed and that nearly everybody is infected with the agent at some time (2,5). C. pneumoniae is currently of considerable interest because of its link to atherosclerosis, although it still remains unclear whether the organism plays a role as an etiological agent or only as a bystander (2,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…This finding supports the assumption that antigenic boosting occurs throughout life (1, 2). There have been few seroepidemiologic studies of C. pneumoniae infection amongthe Japanese population, using the MIFtest (3)(4)(5). Our seroepidemiologic studies demonstrated that a very small percentage of children under five years of age show serologic evidence of past infection with C.…”
mentioning
confidence: 81%
“…pneumoniae (5). The prevalence then increases dramatically from ages 5 through 14 years, and by age 20 years approximately 55%of those studied have detectable levels of antibody to the organism.…”
mentioning
confidence: 96%